2016
DOI: 10.3389/fnhum.2016.00150
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Cognitive Training for Executive Functions after Stroke: A Systematic Review

Abstract: Background: Stroke commonly results in cognitive impairments in working memory, attention, and executive function, which may be restored with appropriate training programs. Our aim was to systematically review the evidence for computer-based cognitive training of executive dysfunctions.Methods: Studies were included if they concerned adults who had suffered stroke or other types of acquired brain injury, if the intervention was computer training of executive functions, and if the outcome was related to executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 57 publications
3
55
0
2
Order By: Relevance
“…No transfer effect was detected, which in part corresponds to, and in part is discrepant, with previous findings. Computerized, implicit working memory training has been reported to generate generalized cognitive gains for children with ADHD 51 and for adults following brain injury, including stroke 8,13,52 . However, the current absence of evidence of improvement adds to a number of studies and meta-analyses observing no transfer effect of computerized working memory training 5,53,54 .…”
Section: Can 6 Weeks Of Training With the Cct Program Cogmed Qm Initimentioning
confidence: 99%
See 3 more Smart Citations
“…No transfer effect was detected, which in part corresponds to, and in part is discrepant, with previous findings. Computerized, implicit working memory training has been reported to generate generalized cognitive gains for children with ADHD 51 and for adults following brain injury, including stroke 8,13,52 . However, the current absence of evidence of improvement adds to a number of studies and meta-analyses observing no transfer effect of computerized working memory training 5,53,54 .…”
Section: Can 6 Weeks Of Training With the Cct Program Cogmed Qm Initimentioning
confidence: 99%
“…As no improvement was detected in the untrained tests, neither could we find any correlating or non-correlating changes in white matter integrity. In a systematic review from 2016 of computer-based cognitive training for executive functions in stroke patients only two of twenty studies included brain parameters as measurements of effects 8 . Only one case study used DTI, in which working memory was found to fluctuate in accordance with training phases and rest phases, with corresponding changes in white matter microstructure 24 .…”
Section: Can Relationships Between Changes In Cognitive and Changes Imentioning
confidence: 99%
See 2 more Smart Citations
“…Up until now, the generalization of these improvements from the games to activities of the patient's daily life has not been proven (Van de Ven, Murre, Veltman, & Schmand, 2016;Zucchella, Capone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%